Earthy-musty odour and off-flavour taints in Phayao Lake, Thailand - Supannee Suwanpakdee (2018)
© 2016, Chiang Mai University. All rights reserved. This study aimed to determine and monitor the levels of earthy-musty odour in Phayao Lake water and the microbiota responsible for the production of odorous compounds, geosmin and 2-methylisoboneol. Geosmin was identified as the main odorous substance in both water and lake sediments. It was significantly related (P<0.05) to the density of cyanobacteria in lake water. Five genera of cyanobacteria were identified as the most frequently encountered groups, namely: Microcystis sp., Lyngbya sp., Phormidium sp., Anabaena sp. and Oscillatoria sp. Furthermore, three cyanobacterial genera, were found to be the most dominant and are well known producers of odorous compounds. Geosmin levels were significantly but weakly correlated (r=0.36; P<0.05) to actinomycetes count. Streptomyces spp. were found to be significantly present in the sediment. Analytical results by GC/MS showed that the majority (63%) of Streptomyces spp. isolated from the sediments were geosmin-producers. Consequently, it was suggested that filamentous cyanobacteria, rather than actinomycetes, were the major contributor of earthy-musty odour in Phayao Lake.